Can Thrombocytopenia be Used to Make a Presumptive Diagnosis of Malaria in Patients with Acute Febrile Illness - Akram, Ammad; Gillani, Mehwish; Uttra, Khurshid Muhammad; Gillani, Mehreen; Atiq, Nausheen; Akram, Anam (Pakistan Armed Forces Medical Journal, 2022)
Objective: To ascertain the diagnostic accuracy of thrombocytopenia in making a presumptive diagnosis of malaria in patients with acute febrile illness, keeping thick and thin films as the gold standard. Study Design: Cross-sectional study. Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi Pakistan, from May to Oct 2017. Methodology: A total of 145 patients meeting the inclusion criteria i.e., patients with fever of 10 or less days, age of ≥12 and ≤65 years of either sex were included in the study. Sample for a complete blood picture was taken in Ethylenediaminetetraacetic acid (EDTA) vacutainer. Simultaneously, two slides each with a thick and thin blood smears were made to ascertain absence or presence of plasmodium vivax species (smear positive and smear negative). The diagnostic accuracy was measured using two by two table and applying formulae for specificity, sensitivity, negative and positive predictive value. Likelihood ratio and ROC (Receiver operator curve) was also calculated. Results: Out of 145 subjects, ninety-four patients (64.8%) were males and 51 were (35.2%) females with mean age of 36.76 ± 14.749 years. The specificity, sensitivity, negative and positive predictive value and diagnostic accuracy of thrombocytopenia in making a presumptive diagnosis of malaria in patients having short history of fever, keeping thick and thin films as the gold standard was 68.8%, 81.4%, 64.7%, 84.0% and 77.2% respectively. Conclusion: Hematological abnormalities are encountered in malaria. Thrombocytopenia has a very good sensitivity and good specificity for malaria.